The Koala Part-of-Speech Tagset for Written Swedish - Yvonne Adesam; Gerlof Bouma (Northern European Journal of Language Technology)
We present the Koala part-of-speech tagset for written Swedish. The categorization takes the Swedish Academy grammar (SAG) as its main starting point, to fit with the current descriptive view on Swedish grammar. We argue that neither SAG, as is, nor any of the existing part-of-speech tagsets, meet our requirements for a broadly applicable categorization. Our proposal is outlined and compared to the other descriptions, and motivations for both the tagset as a whole as well as decisions about individual tags are discussed.